1977
DOI: 10.1128/aac.11.4.708
|View full text |Cite
|
Sign up to set email alerts
|

Cefazaflur, a New Parenteral Cephalosporin: In Vitro Studies

Abstract: Cefazaflur was tested in vitro against 262 strains of bacteria. Inhibitory and bactericidal concentrations were determined with two inoculum sizes of bacterial cells in Mueller-Hinton broth and nutrient broth. Agar dilution studies also were performed. When tested in agar, 5.0 ,ug or less of cefazaflur per ml inhibited almost all strains of Staphylococcus aureus, Escherichia coli, Klebsiella, and Proteus mirabilis. The drug was less active against Enterobacter and indole-positive Proteus, and 7.5 ug of antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…It has been realized that a trifluoroethyl group (SCH 2 CF 3 ) can confer greater activity than other fluoroalkyl groups in many pharmacological studies, which makes the SCH 2 CF 3 moiety an interesting group with respect to the design of bioactive molecules. Examples of fluoroalkylthiolated drugs and agrochemicals including Toltrazuril, Cefazaflur, Flomoxef sodium, Pyriprole, Losartan analogues and Polythyazid are shown in Figure .…”
Section: Figurementioning
confidence: 99%
“…It has been realized that a trifluoroethyl group (SCH 2 CF 3 ) can confer greater activity than other fluoroalkyl groups in many pharmacological studies, which makes the SCH 2 CF 3 moiety an interesting group with respect to the design of bioactive molecules. Examples of fluoroalkylthiolated drugs and agrochemicals including Toltrazuril, Cefazaflur, Flomoxef sodium, Pyriprole, Losartan analogues and Polythyazid are shown in Figure .…”
Section: Figurementioning
confidence: 99%
“…Several authors have reported broth MICs for certain cephalosporins to differ considerably from those obtained with agar dilution (3,11). Thus, it has recently been reported that certain strains of Enterobacter and indole-positive Proteus show higher MICs in broth than on solid medium (2, 6) when tested against cefamandole.…”
mentioning
confidence: 99%
“…Toltrazuril is a coccidiostatic drug in veterinary medicine ,. Cefazaflur, a parenteral cephalosporin, is an important antibiotic drug ,. Fipronil, a widely used phenylpyrazole insecticide, has many advantages over previous generations of insecticides such as organophosphates, carbamates and pyrethroids, (Figure ).…”
Section: Figurementioning
confidence: 99%